The Effect of Lemongrass Leaf and Betel Leaf Extract Ratio Variations on the Optical Characteristics and Crystal Structure of Silver Nanoparticles Synthesized via Green Synthesis - Nirmala Rahima Suci; Riri Jonuarti; Leni Aziyus Fitri; Fandi Oktasendra (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Green synthesis of silver nanoparticles (AgNPs) provides an environmentally sustainable approach by utilizing plant-derived bioactive compounds as reducing and stabilizing agents. The combination of lemongrass (Cymbopogon citratus) and betel leaf (Piper betle L.) extracts may enhance AgNP formation because both contain flavonoids, phenolic compounds, citral, eugenol, and other secondary metabolites. This study aimed to investigate the effects of different lemongrass-to-betel leaf extract ratios on the physical characteristics of AgNPs synthesized through a green synthesis method. AgNPs were prepared using extract ratios of 1:1, 3:1, and 1:3 and characterized using UV–Visible spectroscopy, particle size analysis (PSA), and X-ray diffraction (XRD). UV–Visible spectroscopy confirmed AgNP formation through surface plasmon resonance absorption bands in all samples, with maximum wavelengths of 419, 444, and 398 nm and absorbance values of 1.98, 1.98, and 2.47 for the 1:1, 3:1, and 1:3 ratios, respectively. PSA showed average particle sizes of 39.1 ± 0.9 nm, 59.7 ± 16.1 nm, and 47.2 ± 4.6 nm, with the smallest particle size obtained at the 1:1 ratio. XRD analysis confirmed that all samples possessed a face-centered cubic crystalline structure, with average crystallite sizes of 16.72 nm for the 1:1 ratio, 14.72 nm for the 3:1 ratio, and 9.37 nm for the 1:3 ratio. These findings demonstrate that variations in the composition of the dual-bioreductant system influence the optical properties, particle size, and crystallite size of the synthesized AgNPs. The 1:1 ratio produced the smallest hydrodynamic particle size, whereas the 1:3 ratio yielded the highest absorbance and smallest crystallite size. This study contributes to the optimization of plant-mediated AgNP synthesis by demonstrating that the relative composition of lemongrass and betel leaf extracts is a critical parameter for controlling nanoparticle characteristics.